The Caithness Mermaid, Female Testimony, and the Production of Coastal Knowledge - Garner, Katie (Romanticism on the Net, 2022)
In 1809, Elizabeth Mackay was walking on the beach a short distance from her home in Reay, Caithness, when she saw a mermaid in the water. Her detailed and deeply mysterious account of what she saw caused a national sensation when it appeared in the press. Whether a hoax intended to draw investment and tourists to Caithness or a genuine document, Elizabeth Mackay’s testimony is worthy of close reading, as it documents a rare coastal encounter between a human and a marine animal and the partial connections forged between them. The first part of this article sets her observations in the context of other “strange” phenomena encountered on Scotland’s northern coastline and draws on feminist materialist approaches to read her testimony as an example of what Donna Haraway calls “situated knowledges”—partial, subjective, and most importantly, embodied encounters that oppose an Enlightenment model of all-seeing, detached objectivity. The second part traces the influence of the Caithness mermaid on literary production during the following decade by Christian Isobel Johnstone, Thomas Love Peacock, and Walter Scott. Despite attempts to memorialise the Caithness mermaid in verse, the sighting had a stronger literary afterlife in satirical fiction than it did in poetry.